2018
DOI: 10.1186/s12958-018-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits 17β-estradiol-induced migration, invasion and epithelial-mesenchymal transition in normal and endometriotic endometrial epithelial cells

Abstract: BackgroundMelatonin is a potential therapeutic agent for endometriosis, but its molecular mechanism is unclear. Here, we investigated the effect of melatonin on the epithelial-mesenchymal transition (EMT) in endometriotic endometrial epithelial cells and explored the pathway that might be involved.MethodsThis hospital-based study included 60 women of reproductive age using the endometrium for immunohistochemistry, 6 women of reproductive age undergoing bilateral tubal ligation and 6 patients with endometriosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
2
30
0
2
Order By: Relevance
“…Since EMT is involved in the pathogenesis of endometriosis, 2 , 22 , 23 , 24 , 25 , 26 , 27 , 28 we measured the expression of E-cadherin, an epithelial marker, and vimentin, a mesenchymal marker, by western blotting, and revealed lower E-cadherin expression and higher vimentin as well as MTA1 expression in EcESCs than those in NESCs ( Figures 3 A and 3D). Moreover, in a mouse endometriosis model, vimentin expression was higher and E-cadherin expression was lower in ectopic tissues than in eutopic tissues in IHC ( Figure 1 F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since EMT is involved in the pathogenesis of endometriosis, 2 , 22 , 23 , 24 , 25 , 26 , 27 , 28 we measured the expression of E-cadherin, an epithelial marker, and vimentin, a mesenchymal marker, by western blotting, and revealed lower E-cadherin expression and higher vimentin as well as MTA1 expression in EcESCs than those in NESCs ( Figures 3 A and 3D). Moreover, in a mouse endometriosis model, vimentin expression was higher and E-cadherin expression was lower in ectopic tissues than in eutopic tissues in IHC ( Figure 1 F).…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of endometriosis involves epithelial-mesenchymal transition (EMT), which is a complex process of epithelial cells transforming into mesenchymal cells. 2 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Transcription factors, such as ZEB1, ZEB2, and the Snail/Slug family, drive the process of EMT, along with the decreased expression of epithelium-related E-cadherin and increased expression of mesenchymal-related vimentin. 32 The ectopic endometrium of endometriosis patients shows significantly increased vimentin and remarkably decreased E-cadherin, compared with eutopic endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent investigation of endometriotic epithelial cells, Qi et al [127] reported that the expression of Notch1, Slug, Snail, and N-cadherin is increased whereas expression of E-cadherin and Numb is reduced in the eutopic endometrium of patients; melatonin, at doses of 1 mM, significantly inhibited E2-induced cell proliferation and attenuated migration and invasion via upregulation of Numb and low activity of Notch in these patient-derived cultured cells. The efficacy of melatonin in EMS has also been documented in a phase II double-blind clinical study; in addition to improving the sleep quality, melatonin regulated the secretion of brain-derived neurotrophic factor (BDNF) while reducing daily pain, dysuria, and dysmenorrhea by 40% [128].…”
Section: The Benefits Of Melatonin In the Treatment Of Endometriosismentioning
confidence: 97%
“…8,16 and other invasive pathological processes unrelated to cancer, such as ademyosis or endometriosis. 17,18 Melatonin can inhibit different cell signaling pathways involved in carcinogenesis, which can explain its relative versatility, underlying its action against different types of cancer. For example, melatonin inhibits proliferation and invasion of glioma cells via repression of miRNA-155, 14 modulates tumor growth in PTEN-mutated gliomas, 11 inhibits the proliferation of gastric cancer cells through regulating the miR-16-5p-Smad3 pathway 13 and inhibits breast cancer cell invasion through modulating DF-1/KLF17/ID-1 signaling pathway.…”
Section: Melatoninmentioning
confidence: 99%